Criminal Liability of Corporations for Environmental Pollution in Indonesia - Bima Agung Wibowo; Sumarno Sumarno; Suci Ramadani (The Future of Education Journal, 2026)
Indonesia is a country governed by the rule of law; therefore, the state must prioritize all forms of the legal system as the foundation for governing the nation. The functioning of the state affects several aspects of life, one of which is criminal offenses against the environment committed by corporations. Corporations can be either legal entities or non-legal entities that possess the same rights and obligations as legal subjects. Criminal offenses committed by corporations have affected environmental stability, which in turn impacts society. As perpetrators, corporations must be held accountable for all forms of environmental damage. Environmental damage caused by corporations can take the form of contamination, pollution, and other acts. Consequently, environmental law works in conjunction with criminal law to address cases involving legal actions by these legal entities. This study analyzes criminal law in holding corporations accountable as perpetrators of environmental pollution in Indonesia. The issue of environmental pollution by corporations has become a serious concern due to its massive and complex impacts on ecosystems and sustainable development. Although the Indonesian legal system—particularly through Law No. 32 of 2009 on Environmental Protection and Management (UUPPLH) and the new Criminal Code (Law No. 1 of 2023) has explicitly recognized corporations as subjects of criminal law, the effectiveness of enforcement.